Covalent fragment libraries in drug discovery. Issue 6 (June 2020) - Keeley, Aaron; Petri, László; Ábrányi-Balogh, Péter; Keserű, György M.
Highlights: Overview on available covalent warheads. Design principles of covalent fragment libraries. Surrogate assay methodologies for testing reactivity. Covalent screening protocols against proteins and the proteome. Collection of recent drug discovery applications. Abstract : Targeted covalent inhibitors and chemical probes have become integral parts of drug discovery approaches. Given the advantages of fragment-based drug discovery, screening electrophilic fragments emerged as a promising alternative to discover and validate novel targets and to generate viable chemical starting points even for targets that are barely tractable. In this review, we present recent principles and considerations in the design of electrophilic fragment libraries from the selection of the appropriate covalent warhead through the design of the covalent fragment to the compilation of the library. We then summarize recent screening methodologies of covalent fragments against surrogate models, proteins, and the whole proteome, or living cells. Finally, we highlight recent drug discovery applications of covalent fragment libraries. Teaser: We discuss design principles, screening methodologies, and successful applications of electrophilic fragment libraries for the covalent modification and functional modulation of protein targets of pharmacological interest.